2021
DOI: 10.3390/ijms22094962
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin Causes Transient Changes in TRPM8 Channel Activity

Abstract: Oxaliplatin is a third-generation platinum-based anticancer drug that is widely used as first-line treatment for colorectal carcinoma. Patients treated with oxaliplatin develop an acute peripheral pain several hours after treatment, mostly characterized by cold allodynia as well as a long-term chronic neuropathy. These two phenomena seem to be causally connected. However, the underlying mechanisms that trigger the acute peripheral pain are still poorly understood. Here we show that the activity of the transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
(80 reference statements)
0
8
0
Order By: Relevance
“… Colburn et al (2007) used CCI rodent model to observe significant sensitivity to acetone application. In contrast, TRPM8 gene deletion mice showed no significant increase in acetone sensitivity at any time after ligation ( Rimola et al, 2021 ). This sensory disturbance was also successfully reversed by TRPM8 mRNA antisense ( Su et al, 2011 ).…”
Section: Analgesic Mechanism Of Mentholmentioning
confidence: 99%
See 1 more Smart Citation
“… Colburn et al (2007) used CCI rodent model to observe significant sensitivity to acetone application. In contrast, TRPM8 gene deletion mice showed no significant increase in acetone sensitivity at any time after ligation ( Rimola et al, 2021 ). This sensory disturbance was also successfully reversed by TRPM8 mRNA antisense ( Su et al, 2011 ).…”
Section: Analgesic Mechanism Of Mentholmentioning
confidence: 99%
“…Oxaliplatin treatment has been shown to induce an increase in TRPM8 expression in DRG ( Kawashiri et al, 2012 ; Mizuno et al, 2014 ; Yamamoto et al, 2018 ), and that oxaliplatin-induced cold hypersensitivity is diminished in TRPM8 knockout mice ( Descoeur et al, 2011 ). Recently updated studies have shown that the activity of the TRPM8 but not the activity of any other member of the TRP channel family is transiently increased after oxaliplatin treatment ( Rimola et al, 2021 ). These changes will increase the body’s sensitivity to cold and thus reduce the perception of pathological pain, which may represent a protective effect of self-pain reduction in biological evolution.…”
Section: Analgesic Mechanism Of Mentholmentioning
confidence: 99%
“…It is known that the painful peripheral neuropathy associated with the use of the chemotherapeutic drug oxaliplatin (OXA) is intensified by cold [ 49 ], and that TRPM8 channels play an important role in this debilitating condition [ 18 , 21 ]. In fact, the OXA-induced peripheral neuropathy mice model is being increasingly used to characterize TRPM8 antagonists.…”
Section: Resultsmentioning
confidence: 99%
“…Some channels of the TRP family expressed in nociceptors, like TRPV1, TRPV4, TRPA1 and TRPM8 seem to contribute to this painful, exacerbated sensitivity [ 17 ]. For instance, oxaliplatin (OXA) causes acute and chronic peripheral pain, characterized by cold hypersensitivity, and seems to be related to increased activity of the TRPM8 channels, linked to the activation of phospholipase C and reduction in phosphatidylinositol 4,5-bisphosphate production [ 18 ]. In primary sensory neurons, the overexpression of TRPM8 mRNA and protein in oxaliplatin-induced peripheral neuropathy seems also to be mediated through the c-Myc regulatory gene [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Connected to cancer treatments, it is well known that the administration of oxaliplatin and other chemotherapeutic drugs causes chemotherapy-induced peripheral neuropathy (CIPN), characterized by painful cold allodynia and mechanical hyperalgesia. In a recent article [102], it was demonstrated that oxaliplatin transiently increased the activity of TRPM8 channels 1 h after treatment, while the activity of other members of the TRP channel family was not significantly modified. The activation of phospholipase C (PLC) pathway and the reduction in phosphatidylinositol 4,5-bisphosphate (PIP2) are involved in the possible mechanism.…”
Section: Trpm8 Distribution and Pathological Implicationmentioning
confidence: 99%